Higher education in Southeast Asia : blurring borders, changing balance - Welch, Anthony R. (Routledge research on public and social policy in Asia ;, 2011)
"This is the first book to systematically chart and comparatively assess the trend towards private higher education in Southeast Asia. It includes a substantial analysis of key policy issues, as well as detailed case studies of Indonesia, Malaysia, Thailand, Philippines, and Vietnam"--Provided by publisher.